Ficción televisiva y estereotipos (inter)nacionales : un acercamiento imagológico a El Ministerio del Tiempo (2015-2016) - Enrique Santos Unamuno (Amnis)
From an imagological perspective, this paper focuses on the first two seasons of El Ministerio del Tiempo, a TV series broadcasted in 2015-2016 by the Spanish Radio and Television Corporation (RTVE). First, we briefly introduce the basics and tenets of Imagology, a subfield of Comparative Literature (regardings issues as stereotype / imagotype, character, nation, effet de typique…), traditionally centered on literary texts but susceptible of being applied to other cultural objects (such as audiovisual fiction, which is our case). Secondly, we conduct an imagological analysis of some foreign characters appearing in the series and representing in a stereotypical (imagotypical) way their respective nations (France, USA, Germany or Portugal, to be precise), as far as the national Spanish point of view is concerned. Such analysis is then linked to concepts such as national thought (Joep Leerssen) or Westphalian view (John Agnew) and to the idea of an universal code of particularity expressed by Michael Billig in connection with his concept of banal nationalism.